The Expression ‘Mendokusai’ and Nagi’s Attitude in Blue Lock: Episode Nagi - Salwa Rismilillah Akmalia; Otong Setiawan Djauhari (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2025)
This study investigates the linguistic expression mendokusai as used by the character Nagi Seishirou in the anime Blue Lock: Episode Nagi, examining how this phrase reflects his personal attitude and patterns of social behavior. Mendokusai, commonly found in Japanese youth language, conveys meanings such as “bothersome,” “annoying,” or “too much trouble,” and is often associated with a passive or indifferent tone. Adopting a pragmatics and sociolinguistics framework, this research analyzes the function of the expression within the character’s dialogue and its role in shaping Nagi’s identity as a so-called “lazy genius.” Employing a descriptive qualitative method, the study closely examines selected scenes in which Nagi uses mendokusai across different social and emotional contexts. The findings suggest that Nagi’s repeated use of the phrase is not merely habitual but a deliberate linguistic strategy that highlights his aversion to social expectations, preference for simplicity, and effortless self-assurance. This research demonstrates how the recurrence of a single expression can serve as a significant marker of character identity and behavior, especially in contemporary portrayals of Japanese youth.